Surgical Management of Choke Due to Trichobezoar in a Buffalo - Ahirwar, Manoj K.; Tumariya, Sunil; Gautam, Deepesh; Suman, Alka (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Foreign body syndrome in bovines is a matter of concern in different veterinary practices all over the world. Oesophageal obstruction can be intra-luminal or extraluminal.